Usenamine A: a potential therapeutic agent for rheumatoid arthritis and ankylosing spondylitis through its anti-inflammatory activity - Lee, Yu Jeong; Li, Zijun; Jang, Hyun Hee; Kim, Moon-Ju; Saravanakumar, Kandasamy; Shim, Seung Cheol; Cho, Namki; Won, Eun Jeong; Kim, Tae-Jong (Frontiers in Pharmacology, 2024)
Background Usenamine A (UA) is a natural compound isolated from the lichen Usnea diffracta, and its therapeutic effects on rheumatic diseases are not well understood. This study aimed to evaluate the potential anti-inflammatory effects of UA and its therapeutic effects on rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Materials and methods Molecular docking was performed between the 3D structure of UA and the TNF-TNFR2 complex. Peripheral blood mononuclear cells (PBMCs) from RA and AS patients were treated with UA, and cell viability was measured using the MTS assay and flow cytometry. The in vitro effects of co-culture with UA were determined by measuring inflammatory cytokines, including IFN-γ, IL-17A, and GM-CSF, using flow cytometry and enzyme-linked immunosorbent assay (ELISA). The in vivo effects of UA were evaluated using an arthritis mouse model. Results The docking complex of UA bound to the TNF-TNFR2 complex exhibited docking scores of −5.251 kcal/mol and −6.274 kcal/mol, confirming their active sites. UA did not affect cell viability and suppressed the production of inflammatory cytokines in the PBMCs of RA (IFN-γ, IL-17A, and GM-CSF) and AS (GM-CSF) patients. The ELISA also confirmed reduced cytokine levels in the co-culture of UA and PBMCs from RA or AS patients. In the arthritis mouse model, significantly reduced clinical and histological scores were observed in the UA treatment group. Conclusion Our findings suggest that UA has potential as a binding target for TNF, suppresses inflammatory cytokines in PBMCs, and exhibits anti-inflammatory effects on arthritis in a mouse model.